2020
DOI: 10.1093/fampra/cmaa057
|View full text |Cite
|
Sign up to set email alerts
|

A patient-centredness improvement study for efficacy of behaviour change for healthy lifestyle and weight loss in a student-run free clinic

Abstract: Background Primary care is the ideal place to implement behaviour change interventions for weight management. However, most primary care physicians are not managing patient weight as a standard of care due to lack of knowledge, skills and reimbursement. Generating more physicians who are familiar and comfortable with providing weight management is essential in leveraging a global change. In our university free clinic, medical students provide healthy lifestyle counselling using shared decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, the integrated use of digital health care technology within established clinical pathways aligns with NHS priorities, such as supporting the prevention of obesity-related disease and the transition toward digitally enabled health care [ 10 ]. The current literature provides supportive evidence for the popularity of self-monitoring tools [ 27 ], interactivity with other users [ 28 ] and messages enabling frequent check-ins [ 29 ] among patients attending weight management services generally. A recent narrative review on the use of digital technology in the context of weight management concluded that while evidence exists to support the usefulness of digital interventions in obesity management, this field remains largely unexplored [ 30 ], with a lack of acknowledgment of the role of digital tools within national policies [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the integrated use of digital health care technology within established clinical pathways aligns with NHS priorities, such as supporting the prevention of obesity-related disease and the transition toward digitally enabled health care [ 10 ]. The current literature provides supportive evidence for the popularity of self-monitoring tools [ 27 ], interactivity with other users [ 28 ] and messages enabling frequent check-ins [ 29 ] among patients attending weight management services generally. A recent narrative review on the use of digital technology in the context of weight management concluded that while evidence exists to support the usefulness of digital interventions in obesity management, this field remains largely unexplored [ 30 ], with a lack of acknowledgment of the role of digital tools within national policies [ 31 ].…”
Section: Discussionmentioning
confidence: 99%